Avaliação dos fatores associados à modificações da terapia antirretroviral, em pessoas que vivem com HIV, assistidos em um serviço de assistência especializada do Ceará - Gonçalves, Bruna Leite (2023)
Human Immunodeficiency Virus (HIV) infection is an important public health problem in the world. Scientific development allowed the advent of Antiretroviral Therapy (ART) and provided changes in paradigms. HIV is no longer fatal and has become a chronic and treatable condition. This status conditioned the patient to greater exposure to ART and increased the likelihood of making changes in therapy. The main reasons that can lead to therapeutic changes are: adverse reactions, therapeutic failure and poor adherence to treatment. Therefore, it becomes relevant to assess the factors associated with ART modification and the profile of patients affected by this change. The present study aims to determine the causes of changes in ART and its implications for treatment adherence. The research was developed through a descriptive and retrospective study, using medical records of adults living with HIV, assisted by the Unified Health System - SUS, through a Specialized Assistance Service, in Fortaleza (CE), and who underwent changes in ART between August 2018 to August 2020. The results showed that 22.18% of the sample underwent therapy modification, mostly male, brown skin (or mixed race), aged between 30-49 years. Most patients (76.2%) underwent at least two changes in therapy and the main reasons were the emergence of adverse reactions, followed by the advent of comorbidities, mainly dyslipidemia. The replacement therapeutic options followed the inclusion of new drugs in the Brazilian market and the update of the Clinical Protocol for the management of HIV infection, with the insertion of drugs with a greater safety profile, effectiveness and better dosage. As for the level of adherence to treatment after modifications, 97.9% of the patients had good adherence. Evaluating the immunological parameters, the viral load (> 1,000 copies/ml) before starting ART was 88.13%, after six months of treatment the rate dropped to 25.4%, and the last exams carried out between 2020 and 2021, only 1.70%. TCD4 lymphocytes before treatment, 45.76% had desirable values (>350 cells/mm³), after six months of treatment this number increased to 69.50%, and, based on tests performed between 2020 and 2021, 77.96% of the patients reached the desirable value. The data demonstrate the effectiveness of treatment and the importance of maintaining good adherence to control HIV infection and improve immunity. It can be concluded that the modification of ART is a frequent reality is shown to be an effective strategy for personalization of treatment, bringing benefits such as: increased adherence and immunity, undetectable/non-transmissible viral load, increased survival.